2019
DOI: 10.1108/prt-01-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

Modified sugarcane bagasse for the removal of anionic dyes from aqueous solution

Abstract: Purpose This paper aims to improve the adsorption capacity of sugarcane bagasse (SCB) as a low-cost, attractive and effective adsorbent for dye removal from wastewater. Design/methodology/approach SCB is a cellulosic material; it was chemically modified with compounds containing cationic groups. The adsorption efficiency of unmodified and modified SCB was investigated with anionic dyes by studying various factors that affect modified SCB and adsorption. Findings X-ray diffraction, FT-IR spectra and nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…BB and BFB demonstrated semicrystalline structures with specified cellulose structure peaks of 16.62, 22.34, and 34.34° for BB and specified SiO 2 peaks of 20.94, 26.78, and 50.32° for BFB, as shown in Figure 2 a,b, respectively. 11 , 23 Moreover, it was also found that the specified sodium alginate peaks of 13.54, 18.58, 21.82, and 38.26° resulted from bead formations. 24 BBF and BFBF not only exhibited the specified peaks similarly to BB and BFB but also displayed the specified iron(III) oxide-hydroxide peaks of 21.40, 33.28, 36.84, 41.50, and 53.84° related to JCPDS:29-0713, 25 resulted from adding iron(III) oxide-hydroxide to BP and BFP before synthesizing bead materials, shown in Figure 2 c,d, respectively.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…BB and BFB demonstrated semicrystalline structures with specified cellulose structure peaks of 16.62, 22.34, and 34.34° for BB and specified SiO 2 peaks of 20.94, 26.78, and 50.32° for BFB, as shown in Figure 2 a,b, respectively. 11 , 23 Moreover, it was also found that the specified sodium alginate peaks of 13.54, 18.58, 21.82, and 38.26° resulted from bead formations. 24 BBF and BFBF not only exhibited the specified peaks similarly to BB and BFB but also displayed the specified iron(III) oxide-hydroxide peaks of 21.40, 33.28, 36.84, 41.50, and 53.84° related to JCPDS:29-0713, 25 resulted from adding iron(III) oxide-hydroxide to BP and BFP before synthesizing bead materials, shown in Figure 2 c,d, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…Moreover, the cost–benefit management is also required for industrial applications, so low-cost adsorbents from waste materials might be a good choice to control the operation cost. Many research articles have used various waste materials such as sawdust, coconut shells, potato peels, banana peels, rice husk, bagasse, and bagasse fly ash for dye removal in wastewater. Among these, bagasse and bagasse fly ash are interesting choices because not only they have good chemical properties of cellulose, lignin, and hemicellulose for dye removal but also they help reduce a huge amount of agriculture or industrial waste by acting as recycled waste for the wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Before the treatment of cationization, exposure to plasma nitrogen was successful ineffective PET coloring, which resulted in nitrogen being selected as a working gas with a flow rate of 3 liters/ min [58]. The results also indicated that PET fabric with a very effective surface was achieved by combining the nitrogen plasma and cationization process, leading to better color, weight resilience, traction strength, and ruggedness [57].…”
Section: Highly Efficient Alteration Of Surfaces Employing Plasma Tec...mentioning
confidence: 97%
“…The study is based on the application of an environment-friendly and cationizing effective plasma technology to enhance the hydrophobic nature of polyester (PET) by integrating hydrophilic functions on the PET surface [57]. The results of the study Before cationization with a quaternary ammonium salt, the PET surface was treated firstly with three distinct plasma gases (Quat 188) [58]. In both dyeing and printing operations, madder roots were employed for natural dyes for the green color of PET materials.…”
Section: Highly Efficient Alteration Of Surfaces Employing Plasma Tec...mentioning
confidence: 99%
“…Dyes are used in several areas such as textile, printing rubber, paper, food, cosmetic and plastic production (Abdelghaffar et al , 2019; Martins et al , 2017; Shakoor and Nasar, 2019). Dyes are toxic, carcinogenic and cause serious problems for human and animal health.…”
Section: Introductionmentioning
confidence: 99%